Public Perspective of Indonesia's 2024 Presidential Election in Mopolo Village - Romi Mesra; Putri Christina Mariam Pareda; Elparianti Elparianti; Theodorus Pangalila (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The people in Mapolo Village are the same as those from the rest of Indonesia. The public will be involved in the general election of the president or president in 2024. Given, of course, that the people here have had previous experience with Indonesia’s 2024 presidential election, including scratches and so on, some people feel that whoever the elected leader does not have too much influence on their lives. The aim of this study is to learn more deeply about how perceptions are evolving in society about their involvement in the Indonesia’s 2024 presidential election by the year 2024. In achieving the research objectives, qualitative research methods are chosen, with data collection methods such as observations, interviews and documentation. The results of the research show that the public is very enthusiastic about welcoming the 2024 Indonesia’s 2024 presidential election, the public hopes that the three presidential candidates and vice presidents are politically well and the public judges the three candidate pairs as the best princes of the nation.